The influence of drive energy and geometric characteristics of the cross-section on the deflection of welded I-beams - Palić, Vlastimir; Bela, Sabo (Journal of Production Engineering, 1985)
This paper discusses the results of an extreme experiment in determining the deflection of I-beams resulting from alternating welding of angular joints.